Business Action and Public Education in Brazil - Liliene Xavier Luz (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
This article presents the characteristics participation of Brazilian businessmen on the actions from the political and educational reforms from 1990s. Our focus is based on the changes in the process of social regulation that redefined both the action of the State and the Private Sector, which extended their association areas of activity through interaction with the public authorities. That dynamic process provided for the expansion and participation of multiple actors in the management and provision for Educational Policies, contributing to the diversification way of governing Public Education to go into a partnership and influence them by their organizations. This contextualization, between public and private on education, based on a political rationality the State pluralize the means to govern the education while acting as central actor.